EFFICIENCY AND SMOOTH PRODUCTION FLOW - T. I. Tchepeleva (Наука и техника)
The paper describes modelling and algorithmization of parallel production processes. Method for structurization of a great number of interacting competing production processes is applied for their organization pertaining to interaction of production structure components. The obtained developments can be used for a solution of the problem concerning organization and distribution of a great number of interacting competing processes in engineering industry.